ANALISIS KORELASI REGRESI HUBUNGAN INSENTIF DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN PADA PT. KOBELCO CMI SAMARINDA - Thomas Robert Hutauruk; Sattar; Kahardin (Tinta Nusantara 2018 Vol.1, 2022)
The purpose this study was to determine of relationship between incentives and discipline on employee performance at PT. Daya Kobelco CMI Samarinda. The type of research is quantitative research. A sample of 37 people, all of whom are employees of the company PT. Daya Kobelco CMI Samarinda. The results showed that the work discipline of employees in the company already looks good, so that with this discipline there is comfort in working, so that it will affect the increase in employee work simultaneously based on the F test, the incentive variable and the work discipline variable have a significant effect on employee performance.